Evaluation and Design Recommendation of Interactive Mobile Learning Application for Individuals with Intellectual Disabilities - Hardiyanti, Margareta; Thaha, Taufik Kemal; Arifudin, Nanang; Saputra, Muhardi (Department of Electrical Engineering and Informatics, Vocational College, Universitas Gadjah Mada, 2023)
This study evaluates the usability of an app designed to improve literacy skills in individuals with intellectual disabilities named